2001
DOI: 10.1126/science.1063916
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cutaneous Malignancy by γδ T Cells

Abstract: The localization of gammadelta T cells within epithelia suggests that these cells may contribute to the down-regulation of epithelial malignancies. We report that mice lacking gammadelta cells are highly susceptible to multiple regimens of cutaneous carcinogenesis. After exposure to carcinogens, skin cells expressed Rae-1 and H60, major histocompatibility complex-related molecules structurally resembling human MICA. Each of these is a ligand for NKG2d, a receptor expressed by cytolytic T cells and natural kill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

27
771
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 905 publications
(802 citation statements)
references
References 23 publications
27
771
0
4
Order By: Relevance
“…However, within the tumor microenvironment, the balance between IL-12 and IL-23, which directly reflects Th1 and Th17 cell responses, is shifted toward IL-23 via activation of STAT3 [21,22]. Much attention has been paid to the finding that tumor stromal cells and tumor-associated macrophages, in part by producing IL-23, mainly contribute to the induction of cancer by promoting inflammation, whereas T cells suppress tumor development as part of the immunosurveillance system [23][24][25][26][27][28][29]. Recent research has provided evidence for the involvement of T cells in promoting tumor progression [28][29][30][31][32][33][34][35]; however, the precise effects of T cells and the cytokines they produce on tumorigenesis remain controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, within the tumor microenvironment, the balance between IL-12 and IL-23, which directly reflects Th1 and Th17 cell responses, is shifted toward IL-23 via activation of STAT3 [21,22]. Much attention has been paid to the finding that tumor stromal cells and tumor-associated macrophages, in part by producing IL-23, mainly contribute to the induction of cancer by promoting inflammation, whereas T cells suppress tumor development as part of the immunosurveillance system [23][24][25][26][27][28][29]. Recent research has provided evidence for the involvement of T cells in promoting tumor progression [28][29][30][31][32][33][34][35]; however, the precise effects of T cells and the cytokines they produce on tumorigenesis remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…This observation suggests that, in the case of B16 melanoma cells, IL-17 appears not to be involved in the promoting tumor growth. Resolving the mechanisms underlying these discrepancies would shed light on the regulation of anti-tumor immunity.It has been demonstrated that T cells, including abTCR 1 CD4 1 , abTCR 1 CD8 1 , and gdTCR 1 T cells, play a pivotal role in tumor immunosurveillance to eliminate tumor cells [23][24][25][26][27][28][29]. Recently, it has been shown that abTCR 1 CD4 1 and abTCR 1 CD8 1 T cells also act as tumor-promoting cells in various mouse Eur.…”
mentioning
confidence: 99%
“…Most of circulating  T lymphocytes from humans and primates express the HLA-unrestricted TCR V9V2 which is specific for small non-peptide phosphorylated metabolites (so-called phosphoantigens, PAg) which are frequently up regulated in human tumor cells [4]. NK and  T cells highly express NKG2D (a lectin-like type II transmembrane homodimer), a receptor allowing them to respond to ligands (MICA, MICB and ULBP 1-4) upregulated during oncogenic transformation and stress [5][6][7]. CD16 (a FcRIII receptor) expressed by NK and  T cells plays an important role in Antibody Dependant Cell Cytotoxicity (ADCC) which is of particular clinical interest with the increasing number of anti-cancer therapies using monoclonal antibodies [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…From its part, NKG2D has received considerable attention owing to evidence of its important role in immunosurveillance of tumors [6,7]. Indeed, genotoxic stress that activates DNA damage responses has been shown to induce the expression of NKG2D ligands (MICA, MICB, and ULBPs) and most of established tumor cell lines constitutively express one or more of these NKG2D ligands [43].…”
mentioning
confidence: 99%
See 1 more Smart Citation